ANGREN COAL MINE WORKERS INJURIES LEVEL ANALYSIS - Kurbonov Azimjon Jo’raboy o’g’li; Jalilov Azam Uktam o`g`li; Omonov Rustam Sobirovich; Abduraxmanov Maqsud Zinatulla o’g`li (American Journals Publishing, 2023)
In this article, occupational safety measures should be planned on the basis of management theory, which uses a systematic approach to the development of goals, criteria, methods and management tools. The methodology of the system approach makes it possible to identify the internal connections of the process under study, to identify the main management functions. In an effort to comply with such requirements, organizations define the conditions of their production as affecting the ability of employees to safely perform work.
Keywords: Safety, labor protection, industry, injuries, accidents, accidents, occupational diseases, recommendations, coal mining, risks, violations.